A View of Civil Law and Islamic Law on the Practice of Surrogate Mother - M. Junaidi; Muhammad Ridwan (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2024)
IVF is one of the modern methods that can help legal couples obtain children. Both Indonesian Civil Law and Islamic Law allow this practice. Still, it must be carried out based on the provisions, namely by involving couples who are legal in the eyes of the law. IVF carried out through surrogate motherhood is prohibited by both positive law and Islamic law because its existence can disrupt lineage. Children born from this practice are not considered legitimate due to confusion and ambiguity during the process. This research is a normative juridical literature study that is processed based on primary and secondary legal sources consisting of primary, secondary, tertiary legal materials, and non-legal materials with the aim of: 1) Understand how Indonesian civil law and Islamic law view the issue of surrogate mothers; and 2) Knowing how the guardianship status of IVF children born through surrogacy practices. It was found that both Positive Law and Islamic Law prohibit the practice of IVF with surrogate mothers because it results in legal confusion for the child. This research is expected to contribute to further research, especially research that raises the theme of IVF.